PROCESS COSTING DALAM PERHITUNGAN COST OF GOODS MANUFACTURE SEBAGAI PRICING STRATEGY PADA UMKM PRODUK SEPATU - Popon Rabia Adawia; Aprilia Puspasari (JMB : Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine the cost of good manufacturing (COGM) appropriately so that companies can determine competitive selling prices with the aim of earning the maximum profit. The method used is descriptive comparative with a qualitative approach. Descriptive method is used to describe the production costs incurred in the production process including the cost of raw materials/auxiliary materials, labor costs and factory overhead costs. The calculation results show that to produce shoes, raw material costs Rp. 26,500/pair, auxiliary materials Rp. 8,270.13/pair, labor wages Rp. 24,415.58,-/pair and factory overhead costs Rp. 1443,71,-/pair. So that the COGM calculation results for each pair of shoes is Rp. 60,630. Compared with COGM based on traditional (company calculation) amounting to IDR 55,000 with COGM calculation based on accounting rules, a difference of IDR 5,630 is obtained. This difference is due to calculations that companies do not identify BOP in detail. The COGM calculation appropriately can be the company's strategy to determine the selling price.Keyword: Cost of Goods Manufacture, Pricing, Process Costing, Mass Production